Production of Moringa based Food Flavouring with the Addition of Dried Shrimp - Sebastianus Charmie Wadjong; Mohammad Prasanto Bimantio; Maria Ulfah (CV. Media Inti Teknologi, 2026)
Background: Moringa leaves, rich in essential nutrients like calcium, protein, and antioxidants, are widely valued for their health benefits. However, due to their natural bitterness and strong aroma, they are commonly consumed as capsules or teas rather than incorporated into everyday meals, limiting their market reach.Aim: To increase consumer acceptance, especially among children and adults seeking nutritious foods,